2022
DOI: 10.1029/2021jc017691
|View full text |Cite
|
Sign up to set email alerts
|

On the Processes Sustaining Biological Production in the Offshore Propagating Eddies of the Northern Canary Upwelling System

Abstract: Oceanic mesoscale eddies are ubiquitous structures that constitute an extraordinary laboratory to study the connection between marine physics, biogeochemistry, and biology (Falkowski et al., 1991;Mahadevan, 2014;McGillicuddy, 2016). In spite of their relatively small size that spans from a few tens to a few hundreds of kilometers, mesoscale eddies represent an intrinsic mode of flow of the ocean (Chaigneau et al., 2009;Faghmous et al., 2015), with substantial impact on the lateral transport of momentum and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 93 publications
2
19
0
Order By: Relevance
“…(2014) results are therefore consistent with the findings of our investigation where CEs are associated with positive AOU anomalies across EBUS regions (Figure 2). Elevated levels of production and export of organic material particularly in CEs is supported by a modeling study carried out for the Northern Canary Upwelling System (Lovecchio et al., 2022). Our findings are also consistent with Biogeochemical‐Argo float observations of eddies in the North Pacific Subtropical Gyre, where positive AOU anomalies are observed in CEs, and attributed to enhanced remineralization of sinking particles (Xiu & Chai, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…(2014) results are therefore consistent with the findings of our investigation where CEs are associated with positive AOU anomalies across EBUS regions (Figure 2). Elevated levels of production and export of organic material particularly in CEs is supported by a modeling study carried out for the Northern Canary Upwelling System (Lovecchio et al., 2022). Our findings are also consistent with Biogeochemical‐Argo float observations of eddies in the North Pacific Subtropical Gyre, where positive AOU anomalies are observed in CEs, and attributed to enhanced remineralization of sinking particles (Xiu & Chai, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…The persistence of these events may be associated with the trapping of the initial nutricline doming rather than permanent pumping throughout the event lifetime. Indeed, eddy‐pumping has been shown to contribute very little to the nutrient supply in cyclonic eddies (Dufois et al., 2016; Lovecchio et al., 2022). A detailed identification of the mechanism involved in the formation of each LLP OAXs would require the tracking of the cyclonic eddies and their biogeochemical state to identify what happens in the eddy prior to the OAX initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical models have shown that shoaling of anticyclonic eddy edges coupled with vertical mixing elevate biological productivity relative to the surrounding waters (Lima et al., 2002; Lovecchio et al., 2022; Mahadevan et al., 2008). Similarly, an increase in productivity has been directly observed for warm‐core anticyclonic rings encountered near the Subtropical Convergence south of the Agulhas Retroflection (in this case originating from the Agulhas Current rather than the Retroflection; Dower & Lucas, 1993) and associated with the Gulf Stream (e.g., Gordon et al., 1982; Nelson et al., 1985; Olson & Evans, 1986), as well as in the Bering Sea (Mizobata et al., 2002), Tasman Sea (Scott, 1981), and North China Sea (Wang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%